Estudio de prefactibilidad para la instalación de una planta elaboradora de pirotécnicos recreativos eco - amigables - Tagle Muñoz, Laura Jimena (2020)
The present study seeks to determine the commercial, technical, economic, financial and social viability for the installation of an ecofriendly pyrotechnical factory in terms of the existence of a demand, availability of raw material and appropriate technology at competitive costs in the current situation from Peru. Through the market study, it was possible to estimate that there is an annual demand for the product mix of 672,646 shells for the last year of the project horizon. Furthermore, the bombards are intended for sale to companies that develop fireworks shows. Similarly, given the evaluation of the macro and micro variables for the location, it was possible to identify that the most propitious place to install the plant is Ventanilla. In addition, the technology related to the process is available to be used. Based on this, it was possible to design a plant with an installed capacity that reaches a utilization of 93% in the last year of the project. In addition, the company was categorized as an SME with an estimated revenue volume of 4,615,081 PEN in the first year alone. Finally, the financial economic evaluation was carried out in which the COK for the business resulted in 12.20%. Thus, with regard to the economic scenario, an IRR of 24.72% and an NPV of 1,450,871 PEN was obtained. On the other hand, in a financial scenario in which the machinery, equipment, furniture and EPP is leveraged at a TEA of 15.39%, an IRR of 29.55% and an NPV of 1,574.543 PEN was obtained.